Penerapan Media E-Leaflet Digital Sebagai Upaya Peningkatan Literasi Kesehatan Kasus Trauma Kepala di RS Bhayangkara Surabaya - Aleq, Nur; Prasetyo, Joko; Wahyuni, Ira Trio (Yayasan Daarul Huda Kruengmane, 2025)
Head trauma is an emergency condition that carries the risk of neurological disorders if initial treatment is not appropriate. At Bhayangkara Hospital in Surabaya, patients' families often lack understanding of Basic Life Support (BLS) and first aid. Digital media-based education (e-leaflets) is expected to increase knowledge of BLS/first aid and the preparedness of first responders at the scene and in the emergency room. This community service research used a health education approach through socialization in the emergency room of Bhayangkara Hospital (October 3, 2025), with methods including lectures, discussions, and guidance on the use of e-leaflets. Pre-test–post-test evaluations showed a significant increase in knowledge scores. Obstacles: smartphone access and digital literacy vary. Recommendations: content updates, hospital system integration, and digital literacy assistance for patients/families. The program's success shows an increase in patients' families' understanding of BHD/P3K and the potential for improving the quality of emergency nursing services.